Infinitesimal affine transformations in a tangent bundle of a riemannian manifold with affine connection sΔ=cΔ+vH - Kursat Akbulut; Arif Salimov (Penerbit ukm, 2006)
The main purpose of the present paper is first of all to study conditions for a vertical infinitesimal affine transformation with s c v∇ = ∇ + H in the tangent bundle of a Riemannian manifold and then to apply the results to the study of fibre-preserving infinitesimal affine transformation with s∇